Mathematics Learning Management in integrating 21st Century Skills - Siti Malikah; Sutama Sutama; Achmad Fathoni; Ahmad Muhibbin; Sigit Haryanto (Universitas Dharma Wacana, 2022)
This study was conducted with the aim of describing the planning, implementation and assessment of mathematics learning in integrating 21st century skills at SMA ABBS Surakarta, this research method is qualitative with data sources from the principal, the vice principal of the curriculum section and mathematics teachers for the ICT class program and collection techniques, data by observation, interviews and documentation. The data analysis technique uses Miles and Huberman's interactive model analysis which includes data reduction, data presentation and conclusion drawing. The results of this study include 1) planning learning mathematics by making learning tools that include syllabus, KKM, RPP at the beginning of the school year by referring to the 2013 curriculum. 2) the implementation of mathematics learning based on lesson plans that have been prepared with the integration of 21st century skills and in the mathematics learning process in two languages, namely English and Indonesian, 3) the assessment of mathematics learning is carried out with multiple choice tests, quizzz, kahoot for daily assessments, but for mid-semester assessment and end-semester assessment with the Al Abidin Surakarta portal